Utilizing Teledentistry for Managing Patients: A Systematic Review of Dentist Satisfaction - Jeanette Widjaja; Martina Sinta Kristanti; Adi Utarini (The Journal of Hospital Accreditation, 2023)
Background: The global COVID-19 epidemic has hastened the digital disruption period, resulting in significant technical advancement in dental information and communication via teledentistry. Dentist satisfaction is one of the indicators that is able to reflect the level of technology acceptance, willingness to use, attitude, and confidence of utilizing teledentistry in their daily practices. Dentist satisfaction is crucial to be assessed in conjunction with patient satisfaction. Objective: The aim of the current study was to review dentist satisfaction in using teledentistry. Methods: The current review followed the guideline of JBI Manual for Evidence Synthesis (2021). Four databases were used for searching the articles: PubMed, Medline, Scopus, and ScienceDirect. The last date of search was March, 29th 2023. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart was used to record the selection process and the Mixed Methods Appraisal Tool (MMAT) 2018 was applied to assess quality of the articles. Results: Eleven articles were included in this current review. Four studies were conducted in high income, three studies in middle income, three studies in middle-low income and one study was conducted in multi countries with various level of income. Dentist satisfaction scores ranged from satisfied to very satisfied. Factors influencing satisfaction were classified into five aspects: safety and convenience, quality and access, cost, infrastructure, and referral priorities. Included articles also provided information on challenges in implementing teledentistry, namely: access and infrastructure, financing, user awareness and knowledge, examination and diagnostic processes, and government support. We also identified some recommendations for enhance the implementation: improving audio-visual devices and access, maintaining data privacy, increasing remuneration, increasing training time and implementing formal curriculum of teledentistry, conducting case selections, and enforcing the use of evidence-based policies. Conclusions: Implementation of teledentistry is promising as most dentists were satisfied and received benefits from it. Feasibility studies prior to the implementations of teledentistry must be planned collaboratively amongst dentists, policymakers and insurance agencies to ensure proper implementation. Future studies should explore the use of teledentistry in lower income or developing countries to add information related to cost and infrastructural structure.